Biogas production from selected crop residues in Nigeria and estimation of its electricity value. (1st January 2015) - Jekayinfa, S.O.; Linke, Bernd; Pecenka, Ralf
The production of biogas from peels of watermelon (WP), banana (BP) and potato (PP) was investigated in the laboratory scale using the simple single–state digesters of 1.5 L working volume. The digester was fed on a batch–basis with the slurry of WP, BP and PP containing average moisture content of 18% and operated at temperature of 35°C for 30 days. Measured biogas yields for WP, BP and PP were 0.46, 0.42 and 0.56 m3 (kg ODM)-1 respectively after 30 days digestion time. Methane production from WP, BP and PP was 0.23 (49.8%), 0.24 (56.55) and 0.30 (53.2%) m3 (kg ODM)-1 respectively. Results of this study suggest that 24, 080 million and 38, 520 million kWh of electricity can be generated from biogas at a low–end efficiency of 25% and at the high–end conversion efficiency of 40% respectively using only seven prominent energetically available crop residues in Nigeria.